Cognitive predictors of performance in well-trained table tennis players with intellectual disability - Van Biesen, D.; Mactavish, J.; Kerremans, J.; Vanlandewijck, Y. C. (Adapted Physical Activity Quarterly, 2016)
Evidence-based classification systems in Paralympic sport require knowledge of the underlying effect of impairment in a specific sport. This study investigated the relationship between cognition and tactical proficiency in 88 well-trained table tennis players with intellectual disability (ID; 29 women, 59 men, M ± SD IQ 59.9 ± 9.6). Data were collected at 3 competitions sanctioned by the International Federation for Para-Athletes with Intellectual Disabilities (INAS). A generic cognitive test consisting of 8 neuropsychological subtests was used to assess cognitive abilities relevant to sport (reaction time, processing speed, and decision speed; spatial visualization; fluid reasoning; memory; executive functioning; and visual processing). The backward stepwise-regression analysis model revealed that 18% of the variance in tactical proficiency was attributed to spatial visualization and simple reaction time. Applications of these findings resulted in an evidence-based classification system that led to the reinclusion of athletes with ID in Paralympic table tennis and provide the basis for future research in this important area.